2021
DOI: 10.2174/2405520413999201110094015
|View full text |Cite
|
Sign up to set email alerts
|

Natural Coagulants for the Treatment of Water and Wastewater: A Futuristic Option for Sustainable Water Clarification

Abstract: : Many studies reported the application of natural coagulants in removing pollutants with the help of the coagulation process, and coagulants showed their efficiency in comparison to the literature available. Yet, the utilization or acceptance of these coagulants in treating industrial wastewater is very low. Thus, there is a need for a strategy for enhancing the potential usage of coagulants for water treatment, presenting prevailing options and efforts for the development of coagulants. The utilization of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…The adsorption is governed by external factors like temperature, pH, etc. (Zadinelo et al 2018;Karnena and Saritha 2021). Similar results were obtained by Chung (2006), wherein the concentrations of orthophosphate after treatment were found to be acceptable for discharge into natural waters.…”
Section: Discussionmentioning
confidence: 54%
“…The adsorption is governed by external factors like temperature, pH, etc. (Zadinelo et al 2018;Karnena and Saritha 2021). Similar results were obtained by Chung (2006), wherein the concentrations of orthophosphate after treatment were found to be acceptable for discharge into natural waters.…”
Section: Discussionmentioning
confidence: 54%
“…According to Manoj and Vara (2021), coagulants showed their effectiveness in comparison with the available literature. However, the use or acceptance of these coagulants in industrial wastewater treatment is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Karnena et al, 2021 [86] reviewed the NOM characteristics and showed how the cations interact with the natural organic matter. Later Karnena et al, 2022 [87] removed the NOM from the wastewater using the coagulation techniques and stated that scaling up of studies are required for moving these techniques to be adopted by the water industry [88][89][90].…”
Section: Theory Of Coagulationmentioning
confidence: 99%